2020
DOI: 10.1039/c9nr09867d
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped carbon coated bismuth nanorods with a hollow structure as an anode for superior-performance potassium-ion batteries

Abstract: We designed the Bi nanorods encapsulated in N-doped carbon tubes with hollow structure, which can limit the large volume change during the potassiation process. The composite exhibits superior electrochemical performance as anode for K-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…90.8 mAh g −1 due to the formation of SEI film. Noticeably, the first CE value of the 850‐Bi@N‐CNCs is somewhat higher than other reported Bi‐based anodes (Supporting Information, Table S1) [3, 5–7, 17, 19–24] . Upon the second discharge‐charge cycle, the CE is increased rapidly up to ca.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…90.8 mAh g −1 due to the formation of SEI film. Noticeably, the first CE value of the 850‐Bi@N‐CNCs is somewhat higher than other reported Bi‐based anodes (Supporting Information, Table S1) [3, 5–7, 17, 19–24] . Upon the second discharge‐charge cycle, the CE is increased rapidly up to ca.…”
Section: Resultsmentioning
confidence: 66%
“…79.1 mAh g −1 after 1000 cycles at 5.0 A g −1 (Supporting Information, Figure S21). One especially notes that the high‐rate cycling properties of the 850‐Bi@N‐CNCs anode evidently surpass other reported Bi‐based anodes (Supporting Information, Table S1) [3, 5–7, 17, 19–24] …”
Section: Resultsmentioning
confidence: 87%
“…Many studies in LIBs and SIBs have demonstrated that nitrogen-doped carbon can simultaneously improve the conductivity and the electrochemical activity of carbon materials to accelerate the reaction kinetics. Applying to PIBs, Li et al [155] fabricated a novel structure of a bismuth nanorod in hollow N-doped carbon (Bi@N-CT), which exhibited unexceptional cycle stability (266 mAh g −1 at 10 C over 1000 cycles, ≈0.012% decay rate per cycle) and rate performance (297 mAh g −1 at 20 C, 94% capacity of that at 1 C). Based on the similar considerations, Xiang et al [156] reported evaporation-induced formation of hollow bismuth@N-doped carbon nanorods with an annealing temperature of 920 °C (Bi@C-920).…”
Section: Structural Design Of Bi-based Materials In Pibsmentioning
confidence: 99%
“…Annealing method 0.01-3.0 -327 (600, 0.1 A g −1 ) 430,320,140 (0.1-0.5-1 A g −1 ) [153] Bi@3DGF Space-confined super-assembly strategy 0.1-1. 8 51.1% 164 (400, 1 A g −1 ) 258,154,113(0.1-5-10 A g −1 ) [154] Bi@N-CT Hydrothermal method 0.1-1.5 -266 (1000, 10C) 316,310,297 (1-5-20 C) [155] Hollow Bi@C nanorods In situ reduction and carbonization 0.01-1.6 59.7% 179.1(300, 0.5 A g −1 ) 322.7,221.3,162 (0.1-1-1.5 A g −1 ) [156] Bi@N-C nanosheets Solvothermal approach 0.1-1.5 48% 256(500, 5 A g −1 ) 345,320,266(2-10-20 A g −1 ) [157] Bi@N-C nanospheres Solvothermal approach 0.…”
Section: Ucf@cns@binmentioning
confidence: 99%
See 1 more Smart Citation